Pemakaian Serbuk Ban Untuk Paving Blok Bentuk Heksagon (Segi Enam) - Ridho Rahman, Tengku Muhammad Fahri, Adinda Juwita Nasution, (Jurnal Pusat Studi Pendidikan Rakyat, 2024)
Paving blocks are one of the elements that are often found in building structures, because paving blocks are easy to print and maintain. Paving blocks mixed with tire powder have a light weight so that they do not overload the structure in building construction.This study aims to test the strength of paving blocks in the laboratory mixed with tire powder with a content of 0%, 5%, 10%, 20%, and 30% of the volume of sand. The paving blocks tested were hexagon-shaped. The results showed the same trend as shown by previous studies. The more tire powder content in the paving block, the shock strength of the paving block increases along with the addition of tire powder from 20 blows at 0% tire powder content to 58 blows at 30% tire powder content. Of the paving block shapes, hexagon-shaped paving blocks have better performance. The hexagon shape paving blocks produced in this study include quality B paving blocks in accordance with SNI 03-0691-1996 which can be used for parking lot and yard equipment.